Manganese modified structural and optical properties of zinc soda lime silica glasses - Samsudin, Nur Farhana; Matori, Khamirul Amin; Abdul Wahab, Zaidan; Yap, Wing Fen; Liew, Josephine Ying Chi; Lim, Way Foong; Mohd Zaid, Mohd Hafiz; Sheh Omar, Nur Alia (Optical Society of America, 2016)
A series of MnO-doped zinc soda lime silica glass systems was prepared by a conventional melt and quenching technique. In this study, the x-ray diffraction analysis was applied to confirm the amorphous nature of the glasses. Fourier transform infrared spectroscopy shows the glass network consists of MnO4, SiO4, and ZnO4 units as basic structural units. The glass samples under field emission scanning electron microscopy observation demonstrated irregularity in shape and size with glassy phase-like structure. The optical absorption studies revealed that the optical bandgap (